Beneficial Effects of Pomegranate Fruit Consumption in Cardiovascular Diseases Prevention - Benchagra, L.; Hajjaji, A.; Ramchoun, M.; Khalil, A.; Berrougui, H. (Journal of Nutritional Therapeutics, 2019)
Oxidative stress, dyslipidemia, hypercoagulability, endothelial dysfunction and inflammation are key elements in the development of atherosclerosis. Oxidative stress has been implicated as well in most of the key steps in the pathophysiology of atherosclerosis and the consequential clinical manifestations of cardiovascular diseases. In addition to the formation of atherosclerosis, oxidative stress acute thrombotic events, including dyslipidemia, the oxidation of low-density lipoproteins (LDLs) and plaque rupture leading to atherothrombosis and myocardial infarction. In the last decades, multiple experimental studies and clinical trials have demonstrated that diet plays a central role in the prevention of atherosclerosis. Pomegranate (Punica granatum L.) is one of nature’s most concentrated sources of antioxidants. It contains some very potent antioxidants (i.e. tannins, anthocyanins and flavonoids), which provide a wide spectrum of action against free radicals and are considered to be potent anti-atherogenic products. These properties make pomegranate a healthy fruit with a high potential in preventing cardiovascular diseases. In this review, we give an overview on the newest insights in the role of pomegranate in therapy of vascular diseases.